Detection and activity assessment of primary coronal caries lesions: a methodologic study (2007)
This study has three main objectives: Study (1) test the reproducibility and accuracy of the ICDAS I and ICDAS II caries detection systems; Study (2) validate a new impression material (Clinpro, 3M ESPE), which is said to detect lactic acid in plaque fermenting sucrose; Study (3) devise and test a scoring system for the assessment of caries activity of coronal lesions. Study (1): 141 extracted teeth were examined by two examiners using the ICDAS I and ICDAS II caries detection systems and validated against a histological classification system. Study (2): The accuracy of the impression material in predicting plaque with pH lower/higher than 5.5 was determined in an in situ study of 45 root dentin specimens by comparing the color change in the impression with the actual pH of the plaque, determined with a pH meter. Study (3): A scoring system to assess lesion activity was devised based on the predictive power of the visual appearance of the lesion (ICDAS II system), location of the lesion in a plaque stagnation area and, finally, the tactile feeling, rough/soft or smooth/hard, when running a perio-probe over the lesion. The accuracy was tested in a clinical study of 35 children with 225 lesions/sound surfaces and was validated using the Clinpro impression material for construct validity. Study (1): Intra- and inter-examiner reproducibility was found to be excellent (Kappa-values > 0.82) and the associations strong (Spearmans correlation coefficients > 0.90). Study (2): The Clinpro impression material was found to be acceptable as compared to the results of a pH meter, the combined sensitivity and specificity was 1.63. Study (3): ROC analysis showed that the devised classification system for determining lesion activity had acceptable accuracy (area under curve = 0.84 and the highest combined sum of specificity and sensitivity was 1.67). Thus, it is possible to predict lesion depth and assess the activity of primary coronal caries lesions accurately by using the combined knowledge obtained from visual appearance, location of the lesion and tactile sensation during probing.